Žemaičių savarankiškos raidos pradžia - Girdenis, Aleksas (Baltistica, 1994)
THE BEGINNING OF THE DIVERGENT EVOLUTION OF THE ŽEMAITIAN DIALECTProceeding with presumptions and conclusions expressed earlier (Girdenis, 1971; 1992a), an attempt is made to show that the Žemaitian (especially North Žemaitian) dialect has preserved a number of word-ending phenomena, the stratification and relative chronology of which approximates the linguistic dating of dialectal divergence to archaeologic dating (cf. Tautavičius, 1981).Žemaitians (or so-called Samogitians) with respect to their language started drifting away from the future Aukštaitians (High Lithuanians) not later than in the VIIth century (ca. 700 A.D.), i.e. at the time when the Common East Baltic was splitting into separate tribal languages. One of those languages was Žemaitian, and it turned into a dialect of the Lithuanian much later - by the processes of linguistics convergence which began and was going on under the conditions of the consolidated Lithuanian state.
Keywords: dialektologija; žemaičiai